Splendor of the Grass - Verlyn Klinkenborg (Symphony in the Flint Hills, 2012)
In the Flint Hills of Kansas, the nation’s last great expanse of tallgrass prairie anchors a world renewed by fire.
Keywords: grass; grassland; annual; burning; fire; burn; sky; land; renewal; tallgreass; prairie; Flint; Hills; habitat; animals; native; nature; Chase County; limestone; windbreaks; farmland; ranchers; pioneer; green; endless; expanse; beauty; agriculture; spring burn; big bluestem; little bluestem; flourish; grow; ancestral; ecosystem; natural